2011
DOI: 10.1016/j.ijnurstu.2011.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Patient demographic characteristics and facial expressions influence nurses’ assessment of mood in the context of pain: A Virtual Human and lens model investigation

Abstract: Background Sex, race, and age disparities in pain assessment and treatment have been reported in the literature. However, less is known about how these demographic characteristics influence nurses’ assessment of the emotional experiences of patients who are in pain. Objectives To investigate the influence of patient demographic characteristics and facial expressions on nurses’ assessment of patient mood in the context of pain. Design A cross-sectional study employing Virtual Human (VH) technology and lens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…Consistent with previous lens model studies examining pain decision-making [30,31,36], we examined the results of individual-level analyses at both p < .05 and p < .10. The significance level for all group-level analyses was set to p < .05.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with previous lens model studies examining pain decision-making [30,31,36], we examined the results of individual-level analyses at both p < .05 and p < .10. The significance level for all group-level analyses was set to p < .05.…”
Section: Methodsmentioning
confidence: 99%
“…Research has found that there are pain assessment and treatment disparities depending on the patient’s sex, race, and age (Alqudah, et al, 2010; Anderson et al, 2000; Breuer, 2010; Hirsh et al, 2009a; Hirsh et al, 2011). Women and minorities are less likely to receive opioid analgesics than their demographic counterparts, post-surgery, while in emergency rooms, and for cancer pain (Calderone, 1990; Chen & et al, 2008; Cleeland et al, 1994; Faherty & Grier, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the lens model approach could be applied to other decision-making processes in the hospitals. Despite assessing pain judgment [16] and diagnosing psychiatric patients [31] introduced in the literature section, the method could be tested for discriminating food poisoning, differentiating chemical toxicity, or diagnosing ST segment elevation myocardial infraction (STEMI) patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hirsh et al [16] used the lens model approach to assess how medical staff use patient characteristics and facial expressions to make pain judgment. Speroff et al [26] used a number of cues and clinical data to build a lens model that conferred the relationship between clinical data and physiological measures of hemodynamic status.…”
Section: Applications Of the Lens Model Approachmentioning
confidence: 99%